Effect of intensity and program delivery on the translation of DPP to worksites: A randomized controlled trial of Fuel Your Life - Wilson, Mark G. (J Occup Environ Med, 2016)
OBJECTIVE: To evaluate the effectiveness of the Fuel Your Life program, an adaptation of the Diabetes Prevention Program, utilizing implementation strategies commonly used in worksite programs – telephone coaching, small group coaching and self-study. METHODS: The primary outcomes of BMI and weight were examined in a randomized control trial conducted with city/county employees. RESULTS: Although the majority of participants in all three groups lost some weight, the phone group lost significantly more weight (4.9 lbs.), followed by the small groups (3.4 lbs.) and the self-study (2.7 lbs.). Of the total participants, 28.3% of the phone group, 20.6% of the small group and 15.7 of the self-study group lost 5% or more of their body weight. CONCLUSIONS: Fuel Your Life (DPP) can be effectively disseminated using different implementation strategies that are tailored to the workplace.